Making a Difference for Kansans, FY2015 - Floros, John D. (My University, 2015)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2015, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN29_2015_01
Keywords: UNN29; Administrative and Research Reports; legislature